Prevalence of Urinary Tract Abnormalities in Children with First Urinary Tract Infection at Tertiary Care Institute of Gujarat - Hardas K Chavda; Madhuben Hardas Chavda (Asian Journal of Clinical Pediatrics and Neonatology, 2021)
Background: Pediatric urinary tract infections (UTIs) are a major health-care issue. UTI may be a harbinger of variety of underlying urinary tract abnormalities. This study was conducted to identify the prevalence of urinary tract abnormality in children following the first episode of UTI. Subjects and Methods: This was a hospital-based prospective observational study conducted in children with culture-proven first episode of UTI attending the outpatient department or admitted in the tertiary hospital of Gujarat over a period of 12 months. During the study period, 80 children were diagnosed as culture proved first UTI. Ultrasonography (USG) abdomen, micturating cystourethrography (MCU), and dimercaptosuccinic acid (DMSA) kidney scan were done. Results: The most common pathogen isolated in urine culture was E. coli. About 17.5% had abnormal finding in USG abdomen. Structural Among them, majority (21.4%) had hydroureteronephrosis. DMSA scan was done in 45 children who showed abnormalities in 11. MCU was done in 32 children, which showed abnormalities in 11. The most common anomaly detected was VUR. Among eight children with VUR, majority 37.5% had Grade I VUR. Conclusion: UTI is a common pediatric problem with the potential to produce long-term morbidity. In children below 5 years, symptoms and signs are non-specific and routine urine examination may not yield persistent findings. Hence, high index of suspicion is necessary. The presence of VUR is a risk for recurrence of UTI and renal scarring.